"Sometimes There Just Aren't Any Words": Using Expressive Therapy With Adolescents Living With Cancer - Baerg, Susan (Canadian Journal of Counselling and Psychotherapy, 2007)
The intense physical, emotional and spiritual challenges that adolescents who live with cancer face on a daily basis require a therapeutic approach that moves beyond traditional talk therapy. This article features the art and poetry of two patients, and details the process of bringing creative, expressive arts into counselling with adolescents living with acute or chronic illness. Through exploration of their art work, the teens find valuable hints to healing, and gain wisdom and insight that begin to soothe their souls. An innovative technique of publicly showcasing expressive works as part of the therapeutic process is also described.